VIOLATING THE RIGHT TO PRIVATE LIFE UNDER THE NEW ROMANIAN PENAL CODE - MIRELA GORUNESCU (Challenges of the Knowledge Society)
It is more and more difficult nowadays that the private life of a person to remain out of other people intervention and out of public visibility. In this context, the present paper is concentrated of a new criminalization included in The New Romanian Penal Code - article 226 from this law. It is about the violation to the right to private life which is for the first time incriminated by the Romanian Penal Code.